(untitled) (Palíndromo, 2014)
This paper aims to discuss the in- fluences that digital technology, techno- logical facilities and mobile devices have on the events of popular manifestations and artivism that are happening all over the world. The primary focus falls upon the events that happened in June 2013 in Bra- zil, by performing a survey on how artivism actions may represent alternative actions in the occupation of the public space. Mo- reover, how the free media may represent a distinct alternative to traditional com- mercial media in the dissemination of in- formation and revealing the importance of projects such as the ‘Revolta da Antena’, developed in Florianópolis, in this context. Reflecting on the proposals of the ‘Revolta da Antena’, based on the idea of freedom of information, it is possible to analyze the opportunities and influences of the ne- twork society in relation to humans and new media in contemporary social con- texts, highlighting new possibilities of inte- raction and social media.